Correlation Between Radiological Grading and Clinical Scoring in Knee Osteoarthritis Patients - Sapkota, Kshitiz; Gautam, Sandesh; Luitel, Prajjwol; Sapkota, Radhika; Pokharel, Sabin (Journal of Nepal Health Research Council, 2024)
Background: Osteoarthritis is characterized by mechanical joint abnormalities, primarily involving articular cartilage and subchondral bone degradation. Diagnosis of knee osteoarthritis relies on American College of Rheumatology criteria, and severity assessment utilizes the Western Ontario and McMaster Universities Osteoarthritis Index score and Kellgren and Lawrence grading. Despite reported associations, discrepancies persist in the correlation between Western Ontario and McMaster Universities Osteoarthritis Index and Kellgren and Lawrence grade.Methods: Descriptive cross-sectional study was conducted at the National Trauma Centre, over six months with consecutive convenience sampling. Demographic and clinico-radiological data were collected. Mean, SD and correlation coefficient was calculated.Results: Consecutive convenient sampling yielded 80 participants meeting American College of Rheumatology criteria, aged 52-81 years, predominantly female (67.50%). Significant positive correlations were identified between age, Western Ontario and McMaster Universities Osteoarthritis Index score, and KL grade. Results showed most cases with Kellgren and Lawrence grade III and strong correlations (r=0.73, p=0.00) between total Western Ontario and McMaster Universities Osteoarthritis Index scores and Kellgren and Lawrence grading. Notably, pain, stiffness and physical functions individually exhibited a significant possitive correlation with Kellgren and Lawrence grading. The study affirms age-related influences on osteoarthritis, emphasizes female predilection, and underscores the importance of assessing both clinical and radiological parameters.Conclusions: In conclusion, this study supports Western Ontario and McMaster Universities Osteoarthritis Index efficacy in dynamic disease assessment and management, especially in settings where radiological examinations may be impractical, thus establishing Western Ontario and McMaster Universities Osteoarthritis Index as a versatile tool for systematic monitoring and intervention in knee osteoarthritis.Keywords: knee osteoarthritis; radiology; rheumatology; scoring; X-Ray.